Напрями підвищення ефективності здійснення організаційних змін на підприємствах сільськогосподарського машинобудування - Гринь, Є. Л.; Степаненко, С. В. (My University, 2018)
У статті розроблено забезпечення ефективності здійснення організаційних змін на підприємствах сільськогосподарського машинобудування, яке об'єднує ряд компонент. З метою реалізації цілей здійснення змін пропонується запровадити трьохрівневу систему цілей та критеріальних показників вимірювання їх досягнення із визначенням порогових значень для організаційного, групового та індивідуального рівнів досліджуваних підприємств для процесів, структури, культури та компетентності кадрів. Для гармонізації інтересів зацікавлених сторін у здійсненні змін пропонуються реалізовувати метод аналізу "вигід та витрат" відповідно сукупності критеріїв, які відображають інтереси кожної зацікавленої сторони. Розглянути рівні виникнення опору (індивідуальний, груповий та організаційний), відповідно до яких запропоновано групи причин опору та методи його недопущення. Для обгрунтування типів подолання опору в залежності від масштабу змін (настройка, помірні перетворення, перебудова та радикальні зміни) з використанням інструментарію нечіткої логіки запропоновано конкретні методи в залежності від типу опору (байдужість, скепсис, опозиція змінам, нетерпінням, непокора та саботаж). Для забезпечення успішності здійснення організаційних змін пропонуються впровадити систему розвитку персоналу, яка об'єднує методи навчання, оцінки, атестації та просування. The article provides for ensuring the organizational changes effectiveness in agricultural machine-building enterprises, which combines a number of components. It is proposed to introduce a three-level system of goals and criteria indicators measuring their achievement of defined threshold values for organizational, group and individual levels companies investigated for the processes, structure, culture and staff competence. It is proposed to implement the method of analysis "benefits and costs" under the totality of criteria that reflect the interests of each stakeholder in order to harmonize the interests of stakeholders in the changes implementation. It is proved that the resistance must be considered as internal risks that may adversely affect the change project implementation: on goals, terms, budget or quality. In accordance with the described strategies, all possible measures should be allocated to preventive measures, those aimed at warning its occurrence, and immediate measures to overcome it. The levels of resistance (individual, group and organizational) are given, according to which the groups of reasons of resistance and methods of its prevention are offered. To substantiate the types of resistance overcome, depending on the scale of change (tuning, moderate transformation, rebuilding and radical changes) using the Fuzzy Logic Toolbox of fuzzy logic, specific methods are proposed (material incentives, social package, career development, negotiation, co-optation, coercion, sanctions for disobedience), depending on the type of resistance (indifference, skepticism, opposition to change, impatience, disobedience, and sabotage). In order to ensure the success of or-ganizational changes, it is proposed to introduce a system of personnel development that combines teaching, assessment, certification and promotion methods. Using of all proposed components in the implementation of organizational changes will ensure the effectiveness of their implementation.
Trends of organizational changes effectiveness improvement in agricultural machine building enterprises
Keywords: організаційні зміни; опір персоналу; методи недопущення опору; методи подолання опору; нечітка система вибору; organizational changes; staff resistance; methods of pre-venting resistance; methods of overcoming resistance; fuzzy selection system